Comparison of chemical composition and antioxidant activity from fresh and dried osage orange (Maclura pomifera) fruits extracts - Maslov, Oleksandr; Komisarenko , Mykola; Kolisnyk, Sergii; Sebii, Solomiia; Kostina , Tatyana; Moroz, Valeriy; Akhmedov, Elshan (Annals of Mechnikov’s Institute, 2023)
Introduction. Osage orange fruit is perspective raw material for developing new medicines with antioxidant and antibacterial properties. In pharmacy for obtaining tincture, infusion and extracts use only dried raw material, but there is question about influence fresh raw material on content of phenolic compounds and pharmacological properties of tincture, infusion and extracts. The aim of work was comparison of chemical composition and antioxidant activity from fresh and dried osage orange (Maclura pomifera) fruits extracts. Materials & methods. The object of the study osage orange fresh and dried fruits. The extracts were prepared using 96, 60, 40, 20% (v/v) ethanol and distilled water. The number of phenolic compounds, flavonoids, and hydroxycinnamic acids was determined by a spectrophotometric analysis method, whereas the antioxidant activity of obtained extracts was evaluated by potentiometric method. Results & discussions. The highest content of phenolic compounds (0.70±0.02% and 0.50±0.02%) and flavonoids (0.39±0.02% and 0.29±0.02%) was in 60% ethanolic M. pomifera fresh and dried fruits extracts, respectively, while amount of hydroxycinnamic acids (0.60±0.02% and 0.41±0.02%) and value of dry residue (11.93±0.12% and 8.59±0.09%) were dominated in 40% M. pomifera fresh and dried fruits ethanolic extracts, respectively. The 60% M. pomifera fresh (70.10±1.40 mmol-equiv./mdry weight) and dried (48.11±0.96 mmol-equiv./mdry weight) fruits extracts had the highest level of antioxidant activity among other extracts. The content of biologically active substances and antioxidant were higher in the M. pomifera fresh fruits extracts than in dried ones. The correlation analysis showed that there was a very high positive correlation of antioxidant activity and total phenolic compounds content, high correlation – total flavonoid, hydroxycinnamic acids content and there was no correlation in case of dry residue. Conclusions. The 60% ethanol is the most appropriate solvent to extract the highest amount of phenolic compounds from osage orange fruits. The extracts from fresh raw material has high content of biologically active substances and antioxidant activity than from dried raw material. The phenolic compounds are the main contribute to the antioxidant activity of osage orange fruits extracts. Thus, the fresh osage orange fruits should be use in the developing and creating phytomedicines with antioxidant property. Key words: Osage orange, fresh and dried fruits, extracts, phenolic compounds, antioxidant activity, correlation